2022
DOI: 10.1001/jamanetworkopen.2022.4042
|View full text |Cite
|
Sign up to set email alerts
|

Estimated COVID-19 Cases and Hospitalizations Averted by Case Investigation and Contact Tracing in the US

Abstract: Key Points Question What are the estimated numbers of COVID-19 cases and hospitalizations averted by case investigation and contact tracing (CICT) programs in the US? Findings This decision analytical model study used CICT program data from 23 jurisdictions and estimated that CICT programs averted 1.11 to 1.36 million cases and 27 231 to 33 527 hospitalizations over 60 days during the 2020 to 2021 winter peak of the pandemic. The upper estimate assumes that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 9 publications
1
39
2
Order By: Relevance
“…Literature is sparse on predictors of willingness to provide key information during a case interview. Lash et al 15 reported that 56% of interviewed persons named contacts, while Rainisch et al 14 reported a median of only 27% (range = 15%-74%) , In contrast to an early report from Washington State, we found racial differences in whether information was provided for contacts. 27 As expected, concerns about privacy and misuse of information were important reasons for declining to share contact information.…”
Section: Discussioncontrasting
confidence: 94%
“…Literature is sparse on predictors of willingness to provide key information during a case interview. Lash et al 15 reported that 56% of interviewed persons named contacts, while Rainisch et al 14 reported a median of only 27% (range = 15%-74%) , In contrast to an early report from Washington State, we found racial differences in whether information was provided for contacts. 27 As expected, concerns about privacy and misuse of information were important reasons for declining to share contact information.…”
Section: Discussioncontrasting
confidence: 94%
“…The impact of case investigation and contact tracing on COVID-19 incidence and hospitalizations is, thus, generally estimated through modeling studies. 11 , 42 …”
Section: Effectiveness and Evaluationmentioning
confidence: 99%
“…Because COVID-19 case investigation and contact tracing had to be implemented rapidly, public health jurisdictions generally devised their own approaches, [8][9][10][11][12][13][14][15][16][17] limiting later assessments of their effectiveness in curtailing SARS-CoV-2 spread to metrics such as the proportion of people with positive test results who completed a case interview within a certain time frame or the number of close contacts elicited per interview. 9,12,[19][20][21][22][23]35,38,41 Many case interviews appear to have resulted in no or few named close contacts 9,35,41 ; whether a bifurcated or joint staffing model was more productive remains unclear.…”
Section: Effectiveness and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling studies support the hypothesis that case finding and contact tracing, when combined with effective isolation and quarantine, can interrupt transmission chains and avert hospitalizations. 19 …”
Section: Lessons Learnedmentioning
confidence: 99%